2009
DOI: 10.1111/j.1708-8208.2009.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cancellous Block Allograft Augmentation Prior to Implant Placement in the Posterior Atrophic Mandible

Abstract: Implant placement in the posterior atrophic mandible following augmentation with cancellous freeze-dried bone block allografts may be regarded as a viable treatment alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
61
1
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 29 publications
6
61
1
10
Order By: Relevance
“…In agreement with a previous study, 31 our IF data show a weakly VEGF fluorescence pattern within osteocyte lacunae in FFB grade 0 and the increase of VEGF fluorescence pattern in FFB after six month of maxillary graft. Several in vitro and in vivo studies, 12,14 have suggested that VEGF enhances osteoblast differentiation, migration and activity 10 and osteoclast recruitment.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with a previous study, 31 our IF data show a weakly VEGF fluorescence pattern within osteocyte lacunae in FFB grade 0 and the increase of VEGF fluorescence pattern in FFB after six month of maxillary graft. Several in vitro and in vivo studies, 12,14 have suggested that VEGF enhances osteoblast differentiation, migration and activity 10 and osteoclast recruitment.…”
Section: Discussionsupporting
confidence: 93%
“…In these, one hundred twenty-two combined REO-GBR procedures were performed. 25 Buccal bone plate measurements were taken immediately after ridge expansion, after implant placement, and 6 month later at the time of implant exposure. Ridge width was measured using a caliper (Iwanson spring caliper, Hu-Friedy, Chicago, IL, USA).…”
Section: Case Selectionmentioning
confidence: 99%
“…25,26 Bone allografts were introduced in the 1970s, 27 but only recently have they been used as onlays for alveolar augmentation. [28][29][30][31] These grafts include mainly fresh-frozen, freeze-dried, or demineralized freezedried bones that are harvested from cadaveric sources, processed, and stored with different techniques. 32,33 Although some studies have reported immunologic reactions using some types of allografts, 34,35 freezedried allografts are unlikely to induce a sensitization response in the host tissue.…”
mentioning
confidence: 99%